Community empowerment through the implementation of innovative designs that are responsive to social needs - Nugraha, Adi; Felycia, Felycia; Yudono, Muchtar Ali Setyo; Sriwijaya, Sayid Bahri (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
This community service initiative was designed to develop and implement innovative programs tailored to address the needs of the community, particularly in the areas of education, health, and the environment. In the education domain, activities such as elementary school teaching and informal tutoring were carried out to boost students’ motivation and improve their comprehension of academic subjects. In the health sector, the program included anti-bullying campaigns, stunting prevention counseling, integrated health post (posyandu) facilitation, and general health screenings—all aimed at increasing community awareness regarding physical and mental well-being. Meanwhile, in the environmental field, the team conducted coconut tree planting and soil bioremediation efforts as a form of environmental preservation and ecological education. The implementation strategy involved direct engagement with the community through several stages: initial observation, program planning, execution, and final evaluation. The outcomes of this initiative indicate enhanced knowledge and active community participation in all three sectors. These results affirm that collaborative and innovative approaches in community service can contribute to sustainable solutions and foster an overall improvement in the community’s quality of life. Pengabdian kepada masyarakat ini dirancang untuk mengembangkan dan melaksanakan program-program inovatif yang disesuaikan dengan kebutuhan masyarakat, khususnya di bidang pendidikan, kesehatan, dan lingkungan. Di bidang pendidikan, kegiatan seperti pengajaran di sekolah dasar dan bimbingan belajar informal dilaksanakan untuk meningkatkan motivasi siswa dan meningkatkan pemahaman mereka terhadap mata pelajaran akademis. Di bidang kesehatan, program ini mencakup kampanye anti perundungan, konseling pencegahan stunting, fasilitasi posyandu, dan pemeriksaan kesehatan umum—semuanya bertujuan untuk meningkatkan kesadaran masyarakat mengenai kesejahteraan fisik dan mental. Sementara itu, di bidang lingkungan, tim melakukan penanaman pohon kelapa dan upaya bioremediasi tanah sebagai bentuk pelestarian lingkungan dan pendidikan ekologi. Strategi pelaksanaannya melibatkan keterlibatan langsung dengan masyarakat melalui beberapa tahap: observasi awal, perencanaan program, pelaksanaan, dan evaluasi akhir. Hasil dari inisiatif ini menunjukkan peningkatan pengetahuan dan partisipasi aktif masyarakat di ketiga sektor tersebut. Hasil ini menegaskan bahwa pendekatan kolaboratif dan inovatif dalam pengabdian kepada masyarakat dapat berkontribusi pada solusi berkelanjutan dan mendorong peningkatan kualitas hidup masyarakat secara menyeluruh.